Morphological and Thermodynamic Comparison of the Lesions Created by 4 Open-Irrigated Catheters in 2 Experimental Models. - Moreno, Javier; Quintanilla., Jorge G.; Molina-MorÚA, Roberto; GarcÍA-Torrent, MarÍA JesÚS; Angulo-HernÁNdez, MarÍA JosÉ; Curiel-Llamazares, Carolina; Ramiro-BargueÑO, Julio; GonzÁLez, Pablo; CaamaÑO, Antonio J.; PÉRez-Castellano., Nicasio; Rojo-ÁLvarez, JosÉ Luis; Macaya, Carlos; et al. (Journal of Cardiovascular Electrophysiology, 2014)
Introduction: New generation open-irrigated catheters aim to improve irrigation efficiency. This may change lesion patterns, challenging operators. Indeed, safety issues have recently arisen. We aimed to experimentally assess 4 open-irrigated catheters, comparing lesion size, safety, and heat transfer. Methods: The thigh lesion model was employed in 6 anesthetized pigs to assess the morphology of perpendicular and tangential lesions (n=140) created by the newer catheters ThermoCoolR ® SF,CoolFlex™ , and BlazerÚ Open-Irrigated, and the standard ThermoCoolR ® , at a constant power of 30 W (60 seconds). To evaluate the propensity for deep-tissue overheating, a set of 120 applications were performed at 50 W (180 seconds) comparing pop rates. Thermal assessment of the lesion generation process (20W, 60 seconds, n = 32) was performed with an infrared camera on bovine ventricular tissue. Results: At 30 W, the newer catheters showed lower temperature readings compared with the ThermoCoolR ® . No major efficacy or safety differences were found at tangential applications; however, at perpendicular applications: (1) the SF at 17 mL/min better preserved the superficial layers and focused its maximum thermal effect deeper, but at recommended flow rates (8 mL/min) it generated the largest superficial lesions; (2) CoolFlex™ created smaller lesions than SF and readily induced steam pops at 50W without temperature control; and (3) no major differences were found comparing Blazer™ Open-Irrigated and ThermoCoolR ® . Conclusions: The lower temperature readings in the newer catheters make them more prone to deliver the maximum programmed power. Under experimental conditions, the SF catheter focuses its maximum effect deeper and the CoolFlex™ can be more prone to induce steam pops at high power settings.